INDOLBUTYRIC ACID IN GEL FOR MINICUTTINGS ROOTING OF Eucalyptus benthamii Maiden & Cambage x Eucalyptus dunnii Maiden - BRONDANI, Gilvano Ebling; WENDLING, Ivar; ARAUJO, Marla Alessandra de; PIRES, Patrícia Pereira (Scientia Agraria, 2008)
The indolbutyric acid (IBA) application in powder or liquid way, to adventitious rooting of Eucalyptus minicutting is realized by some forest companies. However, there is little information about its application in gel way. The purpose of the present study was to test different IBA concentrations, applied in gel, on the survival, rooting and vegetative vigor of Eucalyptus benthamii x Eucalyptus dunnii minicuttings. A completely randomized design was used with five IBA concentrations (0, 1000, 3000, 6000 and 8000 mg L-1) and three clones (H22, H23 and H27). The shoots were collected in ministumps cultivated in clonal minigarden, under semi-hydroponic system. After immersion in IBA solutions, the minicuttings were planted in round recipients containing carbonized rice bark and medium vermiculite. There was no interaction between the clone and IBA concentration factors for all the characteristics evaluated. Nevertheless, there was significant difference between the clones referent to the survival in greenhouse and shadow house exits. The leaves per shoot number and the mean length of shoots varied significantly between clones, during evaluation under outdoor conditions. Concerning the IBA concentrations, a quadratic behavior was observed, with maximum efficient technical dose estimated in 4421.9 mg L-1, independent of the clone. This concentration corresponded to an estimation of 43.2% of rooted minicuttings, which characterize good perspectives for IBA in gel use.